Prevalence of low birth weight babies and its association with socio-cultural and maternal risk factors among the institutional deliveries in Bharatpur, Nepal - Bansal, Prerna; Garg, Sandeep; Upadhyay, Hari Prasad (Asian Journal of Medical Sciences, 2018)
Background: The low birth weight (LBW) is considered as sensitive index of nation’s health and development. Almost a third of the newborn in the South East Asia region is low birth weight. Over three- quarters of newborn deaths in Nepal occur in low birth weight babies. The causes of low birth weight are multi-factorial and birth weight is determined by the interaction of both socio-demographic and biological factors. Aims and Objective: To find out the prevalence of low birth weight babies among institutional deliveries and its association with socio-cultural and maternal risk factors. Materials and Methods: A hospital based cross-sectional study was undertaken comprising of 220 postnatal mothers along with singleton live born baby delivered in College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal during the study period of April 2011 to March 2012. Binary logistic regression was used to find the association between dependent variable (LBW) and independent variables. Model accuracy test in binary logistic regression was done by using Hosmer and Lemeshow Test . To find the strength of binary logistic regression Pseudo R-square was used. Results: Out of 220 respondents, the prevalence of LBW was 23.6% (with 95% CI 21.88 to 25.32%). The risk factors like rest received in afternoon during pregnancy, dietary intake during pregnancy and period of gestation were found to be statistically significant. The odds of having LBW babies was 9.07 times higher in preterm births, 2.44 times higher among mothers who took afternoon rest of less than two hours and 3.44 times higher among those mothers who took dietary intake less or same as before during pregnancy. The variation in LBW due to these factors was found to be 22.9% to 34.4%. Conclusion: The prevalence of low birth weight was found to be significantly high among institutional deliveries of this region of the country. Socio-cultural and maternal risk factors like rest received in the afternoon during pregnancy, dietary intake during pregnancy and period of gestation were found to be significantly associated with low birth weight babies. The problem of low birth weight babies can be lessened down as most of these factors can be tackled easily by providing adequate and effective antenatal care services with its maximum utilisation as well as home care by emphasising upon education of mothers and family members, hence decreasing infant and child mortality rates.